2017
DOI: 10.1186/s40557-017-0163-2
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to sharps injury among healthcare providers in Ethiopia regional hospitals

Abstract: BackgroundSharps injury is a penetrating stab wound from a needle, scalpel, or another sharp object that may result in exposure to blood or other body fluids. According to World Health Organization pooled estimate, the annual incidence of sharps injury in Africa was ranged from 2.10 to 4.68 per person per year, but research data in Ethiopia is limited. The aim of the study was to investigate sharps injury prevalence and associated risk factors.MethodsInstitution based cross-sectional study was conducted with 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 24 publications
5
27
0
Order By: Relevance
“…Nurses in both facilities had the highest exposure see Table 4. This is consistent with many other studies; 62.6% of nurses in a study in Ethiopia had been exposed to blood/body fluids [21]. Another study on blood and body fluid exposure in African health care system revealed a high prevalence of HCWs over a 12 month period with a range of 33.9% in South Africa to 60.7% in Northern Africa as the highest, however very few studies have been conducted on Body fluid exposure between 2000 -2017 in African [22].…”
Section: Discussionsupporting
confidence: 92%
“…Nurses in both facilities had the highest exposure see Table 4. This is consistent with many other studies; 62.6% of nurses in a study in Ethiopia had been exposed to blood/body fluids [21]. Another study on blood and body fluid exposure in African health care system revealed a high prevalence of HCWs over a 12 month period with a range of 33.9% in South Africa to 60.7% in Northern Africa as the highest, however very few studies have been conducted on Body fluid exposure between 2000 -2017 in African [22].…”
Section: Discussionsupporting
confidence: 92%
“…More than 45% of HCWs had at least one episode of percutaneous injury. 10 The studies showed that practicing needle recap, 11 cigarette smoking, lack of training on occupational health and safety, job satisfaction, 12 on the job training, 13 work experience, working hours, presence of personal protective equipment, and infection prevention guideline utilization were found to increase the risk of NSSIs. 14 The prevalence of NSSIs can be reduced through the improved training and use of safety devices, education, and awareness.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Cheng et al (2012), the risk of occupational NSIs increased significantly with several factors including number of years in practice, working in clinics, lower compliance with infection control procedures, and having insufficient knowledge of blood-borne pathogens. In another study, a lack of in-service training and previous exposure to sharps injury were statistically significant risk factors for sharps injury, increasing the risk by about 4.7-fold (Sharew et al, 2017).…”
Section: Introductionmentioning
confidence: 99%